¿Están hablando de mí?: Challenges for multilingual organizations. (2014) - ,; ,; ,
Abstract : Purpose – Drawing on social categorization, relational demography, and faultline theories, the purpose of this paper is to examine interpersonal relationships between Hispanic American, European‐American, African‐American, and Asian‐American coworkers in relation to language use in the workplace (English or Spanish).Design/methodology/approach – Employed adults ( n =97) participated in one of four racioethnic‐specific focus groups (Hispanic American, European‐American, African‐American, and Asian‐American) at each of four worksites in order to assess their reactions to working in a linguistically diverse environment. Interviews with onsite management and human resource directors were also conducted.Findings – Language issues created noticeable faultlines between English and Spanish speakers. In total, six themes representing issues for multilingual organizations emerged: inclusion vs exclusion, assimilation vs ingroup identification, essential communications, composition issues, utility of speaking English, and negative affective responses.Research limitations/implications – Results highlight the difficulties inherent in working in multilingual groups and the challenges they present for organizations. Results also suggest the importance of group composition in the development of language issues.Originality/value – This paper is among the first to present insight into the experiences of workers in linguistically diverse workplaces, and the barriers presented by language differences. As the number of Hispanics in the US workforce continues to increase, maintaining effective relationships between Spanish and English speakers at work becomes especially important for organizational success. Suggestions for managing a multilingual workforce are included. Acknowledgements : This research was supported by the National Science Foundation under Grant No. 0519802 to the first author. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the authors and do not necessarily reflect the views of the National Science Foundation. The authors thank Dr Maria Cecilia Zea for helpful comments on an earlier draft of this manuscript.